Gloriana de Britten et le rêve de l’opéra anglais - Gilles Couderc (Revue LISA)
The composition of Benjamin Britten’s sixth opera, Gloriana, originates from a conversation about emblematic national operas, the lack thereof in the British repertory and the need for Britten to compose such an opera to coincide with the Coronation of the young Queen Elizabeth II in 1953. Britten’s insistence on composing such an opera based on the tragic love story between the first Queen Elizabeth and Essex, depicted in Lytton Strachey’s dramatic biography, raises several questions. Why should Britten, the controversial composer of several controversial works, curry royal patronage? Why should he insist on composing for an event of such national significance? Why should Britten ride the hobby horse of a national opera and share the obsession of a national opera common to German composers of the Romantic generation? Gloriana turns out to be one of the elements that point to modernist and cosmopolitan Britten’s great sense of a national identity as a composer and his claim to work within a distinctly English tradition. The Coronation opera is also one of many endeavours in Britten’s production to resuscitate English Opera, his life-long ambition. With Gloriana, Britten once more leads the fight to eradicate English people’s prejudices against musicians in general and their own composers in particular and to give the lie to the dictum that Britain is the country that has no music.